Pengelolaan Lingkungan Hidup Dalam Perspektif Islam - MS. Ka'ban (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
The majority of environment damages are caused by of human actions. Those damages impact to several of natural disasters in the earth like flood, landslide, pollution etc. Actually there were various efforts which have strived to handle environment damages especially by science and technology approach, but aswer know those damages don't stop yet. Based on those facts we need new solution by other approach like approach and participation of religion to handle those problems. Because religion has force relation with the nature and environment. Besides it can convince the people that there is transcendental force of God.